Music - Media - History Re-Thinking Musicology in an Age of Digital Media - Santi, Matej; Berner, Elias (Musik und Klangkultur, 2021)
Music and sound shape the emotional content of audio-visual media and carry different meanings. This volume considers audio-visual material as a primary source for historiography. By analyzing how the same sounds are used in different media contexts at different times, the contributors intend to challenge the linear perspective of (music) history based on canonic authority. The book discusses AV-Documents (analysis in context), methodological questions (implications for research, education, and popularization of knowledge), archives of cultural memory (from the perspective of Cultural Studies) as well as digitalization and its consequences (organization of knowledge).